Challenges Facing Lecturers in Using Virtual Learning to Increase Students' Academic Success - Yuspik Yuspik; Gita Amelia; Ida Ayu Hani Erlina (International Journal of Science Education and Cultural Studies, 2023)
The goal of this study is to identify the difficulties lecturers have when facilitating virtual learning for STKIP PGRI Metro Students at English Education Department. Five English lecturers served as the subjects of this study, which used qualitative descriptive research. Interviews and observations served as the research's primary data collection methods. The Miles and Huberman’s hypothesis has been used to analyse the data in three steps. The study's findings revealed that (a) lecturers face difficulties in the virtual learning process because of students' distance from internet resources, (b) it is challenging to get students and lecturers to explain things clearly, (c) lecturers lack motivation to teach because of students' distance and network issues, and (d) students have limited internet knowledge and it is challenging to start a meeting using a different application. This study shows that there are numerous difficulties when lecturers use virtual learning. Because of their distance from internet sources, the majority of lecturers had problems joining the classroom if the pupils did not participate in virtual classes. The lecturer faces additional obstacles due to their inability to motivate their students to learn. Additionally, the restriction on network access forced the students to respond to the lecturers' explanations and assignments in order to assess their understanding.